1993
DOI: 10.5694/j.1326-5377.1993.tb137529.x
|View full text |Cite
|
Sign up to set email alerts
|

Determining the incidence of different subtypes of stroke: results from the Perth Community Stroke Study, 1989–1990

Abstract: ObjectiveTo determine the incidence and case fatality of seven distinct subtypes of stroke in Perth, Western Australia. Design and settingA population‐based descriptive epidemiological study. SubjectsAll residents of a geographically defined segment of the Perth metropolitan area (estimated population 138 708 persons) who had a stroke or transient ischaemic attack between 20 February 1989 and 19 August 1990, Inclusive. Main outcome measuresThe following subtypes of stroke were classified according to standard … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
38
2
4

Year Published

1999
1999
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(48 citation statements)
references
References 27 publications
4
38
2
4
Order By: Relevance
“…Incidences were reported separately for women and men by age category in 16 studies 5 6 9 10 16 18–20 22 27 45 49 50 52 54 57. In this subset of studies, the women–men ratio ranged from 0.65 (95% CI 0.51 to 0.82) to 1.50 (95% CI 1.07 to 2.10).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Incidences were reported separately for women and men by age category in 16 studies 5 6 9 10 16 18–20 22 27 45 49 50 52 54 57. In this subset of studies, the women–men ratio ranged from 0.65 (95% CI 0.51 to 0.82) to 1.50 (95% CI 1.07 to 2.10).…”
Section: Resultsmentioning
confidence: 99%
“…Twenty studies, including the nine studies with only age specified subsets of the population, reported separately on incidences per age group 5 6 810 16 18–20 22 27 36 45 49 50 52 54 57 60 64. The overall incidence of these 20 studies was 13.9 (95% CI 13.3 to 14.5) per 100 000 person-years.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As noted previously, stroke is a heterogeneous disorder that consists of major pathological types, each of which has differing aetiologies (Donnan, McNeil, Adena, Doyle, O'Malley, et al, 1989;Thrift, McNeil, Forbes, & Donnan, 1996, incidence rates (Sudlow & Warlow, 1997;Petty, Brown, Whisnant, Sicks, O'Fallon, et al, 2000), management (Schievink, 1997; National Institute of Neurological Disorders and Stroke rt-PA Stroke Study Group, 1995), and short to medium-or long-term outcomes (Anderson, et al, 1993;Bamford et al, 1991;Brown, Whisnant, Sicks, O'Fallon, & Wiebers, 1996;Longstreth, Nelson, Koepsell, & van Belle, 1993;Thrift, Dewey, Macdonell, McNeil, & Donnan, 2000). If specific stroke subtypes are shown to have differing neuropsychological outcomes, then the need for community and rehabilitation services, educational and interventional programs in stroke patients and their families could also be different (Sturm et al, 2002).…”
Section: Neuropsychological Outcomes Of Strokementioning
confidence: 96%
“…Because of the poor outcome in patients developing intracerebral haemorrhage,1315 there has been concern that intracerebral haemorrhage might offset the benefits of aspirin treatment, particularly when used in low risk settings such as for the primary prevention of coronary heart disease. 2 16…”
Section: Introductionmentioning
confidence: 99%